2012
DOI: 10.2989/16085914.2011.636902
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in two potential indicator fish species from a hyper-eutrophic freshwater ecosystem in South Africa: a baseline study

Abstract: SummaryHistopathological changes were identified in selected target organs from two freshwater fish species, Clarias gariepinus and Oreochromis mossambicus, inhabiting a hyper-eutrophic freshwater aquatic system. The approach was to use a histology-based fish health assessment protocol which included a semi-quantitative histopathological assessment of six target organs (gills, liver, ovaries, testes, kidney, and heart). Results of water quality analysis showed selected variables to be above the recommended lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…A number of individual fish had OCP levels above the recommended limit for daily human intake as stipulated by the World Health Organisation (WHO) and US Food and Drug Administration (FDA). Studies also showed reproductive abnormalities including intersex in C. gariepinus from the RVD (Barnhoorn et al, 2004;Pieterse et al, 2010) and Oreochromis mossambicus (Peters, 1852) from the RDPD (Marchand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A number of individual fish had OCP levels above the recommended limit for daily human intake as stipulated by the World Health Organisation (WHO) and US Food and Drug Administration (FDA). Studies also showed reproductive abnormalities including intersex in C. gariepinus from the RVD (Barnhoorn et al, 2004;Pieterse et al, 2010) and Oreochromis mossambicus (Peters, 1852) from the RDPD (Marchand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the semi-quantitative assessment was especially important to show the significance of these results, as observed in other studies with fish (Marchand et al, 2012;van Dyk et al, 2012), which also used methodologies based in the work described by Bernet et al (1999).…”
Section: Discussionmentioning
confidence: 66%
“…The studies by Marchand et al. () and Van Dyk et al. () were the first reports of macroscopically visible hepatic nodular alterations in C. gariepinus from Roodeplaat Dam.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the presence of hepatotoxins such as microcystins in the Roodeplaat Dam (Van Ginkel, ; Conradie & Barnard, ). It has been suggested that these hepatotoxins are the most likely cause, of these nodules (Van Dyk, Cochrane, & Wagenaar, ; Marchand, Van Dyk, Barnhoorn, & Wagenaar, ). A number of studies are available that specifically show ultrastructural alterations in fish liver following exposure to microcystins (Li, Xie, & Chen, ; Qiu, Xie, Ke, Li, & Guo, ; Atencio et al., ; Branka et al., ; Mitsoura et al., ).…”
Section: Introductionmentioning
confidence: 99%